НЕКОТОРЫЕ ПРОБЛЕМЫ РЕАЛИЗАЦИИ ГОСУДАРСТВЕННОЙ ГЕНДЕРНОЙ ПОЛИТИКИ В РЕСПУБЛИКЕ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
In given article problems of realization state gender policies are considered. The brief characteristic of work of the National commission onaffairs of family and women at the President of Republic of Kazakhstan is given, it′s structure, basic directions of activity. The National Plan of actionon improvement of position of the women, created on the basis of the Peking Platform of Actions and being by a part of strategy of Kazakhstans 2030is considered, are summed up the done work. The next ways are offered: perfection of the national legislation and practice of it′s application;realization scientific theoretical and applied researches with a view of revealing real position of women and men in economic, social, political andcultural life of a society; development research and educational programs on social problems on the basis gender approach; realization of seminars -trainings, conferences, round tables on problems of development gender relations. All this in a complex will promote reforming of educational spaceof Republic of Kazakhstan from positions gender indicators.